Model for Implementing Profit and Loss Sharing Financing In Sharia Banking in North Sumatra, Indonesia - Sinaga, Fatimah Yanti; Yuslem, Nawir; Siregar, Saparuddin (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This research examines the implementation of profit and loss-sharing financing in Sharia banking in North Sumatra. Profit and loss sharing is where one party, having capital (shahibul maal or rabbul maal), entrusts a certain amount of funds to another party, a business actor (mudharib), to carry out an activity or business. The theoretical basis of this research uses several main theories. The basic theory used in this research is Profit and Loss Sharing (PLS) with two main models, namely mudharabah and musyarakah. The ratification of Law of the Republic of Indonesia No. 21 of 2008 concerning Sharia Banking (UUPS) is a responsive effort to the growth of the Sharia banking industry in Indonesia. The main principle applied is the principle of profit sharing with different characteristics from the interest system, one of which is financing products. Although still faltering, the development of sharia financing has begun to grow significantly both through mudharabah and musyarakah. This research uses a descriptive research approach on qualitative and quantitative data carried out using pairwise comparison questionnaire interviews and documentation. The results are divided into five parts: analysis of research synthesis results, analysis of aspect synthesis results, analysis of problem synthesis results, analysis of solution synthesis results, strategy cluster analysis, and implementation model.